Imlementasi Sistem Otomatis Pengontrol Pembangkit Tegangan Direct Curent (DC) Ke Alternating Curent (AC) Berbasis Android - Daniel Alfa Puryono (LPPM Poltek ST Paul, 2021)
This research article describes the application of bluetooth technology and an android application that can control electricity from Direct Curent (DC) to Alternating Curent (AC) voltages using an inverter and Arduino Uno R3. This system is intended to design automatic control devices that are user-friendly and comfortable to use. The system consists of an inverter, an arduino ATMega328 microcontroller, a relay module, a Bluetooth HC-05 and the MIT App Inventor 2. Arduino controls all connected components using the Integrated Development Environment (IDE). Meanwhile, the relay module is used for the switching mechanism. Only when all the tools and applications become one device can the user control the electrical equipment connected to the inverter's automatic system. So that the system can activate and deactivate household appliances using the android application via the bluetooth module.